Teknik Vocal Riak Pada Lagu Kepesindenan “Ciawian” Versi Ibu Iyan Arliani Dalam Tradisi Karawitan Sunda - Willa Agustina; Sandie Gunara (Journal of Music Science, Technology, and Industry, 2025)
Purpose: This study aims to examine the ripple vocal ornamentation technique in the "Ciawian" kepesinden composition as a manifestation of conventional vocal art in Sundanese gamelan music. Ripple vocal ornamentation is a unique sound decoration and is a distinctive characteristic that distinguishes the Sundanese vocal tradition from other cultural vocal systems. Research method: The research approach applied is a qualitative descriptive methodology with an ethnomusicological perspective, including direct observation, intensive dialogue with gamelan artists, and a study of audio-visual materials for the "Ciawian" kepesinden performance. Results and discussion: The study findings indicate that the ripple vocal ornamentation in the "Ciawian" composition displays a characteristic in the form of soft and directed sound vibrations, which act as melodic decoration to beautify musical expressions. This ornamentation is implemented in specific segments in the song structure, especially at the end of the melodic sentence and parts that require emotional accentuation. Mastering ripple ornamentation requires consistent practice and a deep appreciation of Sundanese musical aesthetics, coupled with the skill of controlling the breathing system and adequate vocal resonance. Implication: This research contributes to the efforts of documenting and conserving traditional Sundanese vocal ornamentation, especially in the realm of kepesinden which is an important element of Sundanese karawitan. The results of this study can be used as a reference for artists, art teachers, and academics who are interested in the development of traditional Indonesian vocal techniques.